A technical examination and discussion of the conservation decision-making process using Anton van Wouw’s Cattle Grazing near Pretoria Zoo (ca. 1896) as case study - McGinn, Isabelle (University of Pretoria, 2023)
Dissertation (MSocSci (Tangible Heritage Conservation))--University of Pretoria, 2022.